The variability of the microbial profile of corneal ulcers - P. M. Maharramov; M. H. Guliyeva (Российский офтальмологический журнал, 2021)
Purpose. To study the microbiological profile of corneal ulcers depending on demographic and clinical characteristics of patients.Materials and methods. 97 patients (114 eyes) (65 men and 32 women) diagnosed with corneal ulcer were tested. 80 patients had unilateral and 17 bilateral ulcers. The patients’ age varied from 15 to 87 years (24.7 % aged 50–59, 27.8 % aged 60–69, and 19.7 % aged 70 or older). All patients were examined for the microbiological profile of corneal scrapings to determine the microbial flora of the corneal ulcer. The significance of gender, age and clinical differences found in the structure of the microbiological profile was evaluated by the the χ² criterion.Results. Gram-positive microorganisms were among the most frequently detected: Staphylococcus epidermidis in 25.3 % of cases, Streptococcus pneumoniae in 21.7 % of cases, Streptococcus viridians in 16.3 % of cases, and Staphylococcus aureus in 7,8 % of cases. Gram-negative microbial flora (Pseudomonas aeruginosa) was revealed in 22.3 % of cases, while fungi were identified in 6.6 % of cases.Conclusion. The microbiological profile of corneal ulcer depends on the patient’s age, localization, size and depth of the lesion, as well as the presence of complication. Severe and complicated forms of corneal ulcer (sized ˃5 mm, depth of the lesion exceeding two thirds of corneal thickness) are often associated with the detection of more than one type of microorganism.